Isoforskolin Alleviates AECOPD by Improving Pulmonary Function and Attenuating Inflammation Which Involves Downregulation of Th17/IL-17A and NF-κB/NLRP3 - Xiao, Chuang; Cheng, Sha; Li, Runfeng; Wang, Yutao; Zeng, Deyou; Jiang, Haiming; Liang, Yaping; Huang, Rong; Pan, Hanxiao; Wu, Xiao; Fang, Yan; Chen, Chen; et al. (Frontiers in Pharmacology, 2021)
Chronic obstructive pulmonary disease (COPD), a major cause of morbidity and mortality worldwide, is widely considered to be related to cigarette smoke (CS), and viral infections trigger acute exacerbation of COPD (AECOPD). Isoforskolin (ISOF) is a bioactive component from the plant Coleus forskohlii, native to Yunnan in China. It has been demonstrated that ISOF has anti-inflammatory effect on acute lung injury animal models. In the present study, we investigated the efficacy and mechanism of ISOF for the prevention and treatment of AECOPD. Mice were exposed to CS for 18 weeks and then infected with influenza virus A/Puerto Rico/8/34 (H1N1). ISOF (0.5, 2 mg/kg) was intragastrically administered once a day after 8 weeks of exposure to cigarette smoke when the body weight and lung function of model mice declined significantly. The viral load, pulmonary function, lung morphology, Th17 cells, and inflammatory cytokines in lung tissues were evaluated. The expression of nuclear factor κB (NF-κB) and NOD-like receptor pyrin domain–containing protein 3 (NLRP3) inflammasome pathways were detected. The results showed that ISOF treatment reduced the viral load in the lung homogenate, decreased the lung index of model mice, and lung pathological injuries were alleviated. ISOF also improved the pulmonary function with increased FEV0.1/FVC and decreased Rn and Rrs. The levels of inflammatory mediators (TNF-α, IL-1β, IL-6, IL-17A, MCP-1, MIG, IP-10, and CRP) in the lung homogenate were reduced after ISOF treatment. ISOF decreased the proportion of Th17 cells in the lung tissues by the flow cytometry test, and the protein expression levels of RORγt and p-STAT3 were also decreased. Furthermore, ISOF significantly inhibited the activation of NF-κB signaling and NLRP3 inflammasome in the lung tissues of model mice. In conclusion, ISOF alleviates AECOPD by improving pulmonary function and attenuating inflammation via the downregulation of proinflammatory cytokines, Th17/IL-17 A, and NF-κB/NLRP3 pathways.